Penentuan Rute Pengiriman Pupuk Urea Bersubsidi di Karanganyar - Yusuf Priyandari; Yuniaristanto .; Yahuda Patria Christiawan (Institute of Research and Community Outreach - Petra Christian University, 2011)
This paper develops a vehicle routing problem (VRP) model for determining the routes in urea fertilizer distribution from a depot to retailers. The distribution is done in work days which uses trucks, each truck can serve more than one route (multiple trips), and each retailer has a time window. The vehicle routing model is built in a mixed integer linear programming (MILP) and the objective function is minimizing total transportation cost. The distances from the distributor to retailers and inter-retailers do not use Euclidian approach but the road network on a digital map in order to make the route solution is more realistic. Historical distribution data was used to test the model. The result shows that the model can minimize the cost about 2.28% which is compared to the original routes.